Enhancing Medical Learners' Knowledge of, Comfort and Confidence in Holding Serious Illness Conversations. (December 2019) - Tam, Vivian; You, John J.; Bernacki, Rachelle
Objectives: Having early discussions with seriously ill patients about their priorities and values can improve their peace of mind and family outcomes during bereavement; however, physicians and medical students report feeling underprepared to hold serious illness conversations. We evaluated the impact of the Serious Illness Care Program clinician training workshop on medical learners' knowledge of comfort and confidence in holding such conversations. Methods: Eligible learners were penultimate- or final-year medical students or first-year residents of generalist programs (Family Medicine, Internal Medicine). Learners participated in a 2.5-hour workshop involving reflection on serious illness discussions, didactic teaching and demonstration of the Serious Illness Conversation Guide (SICG), role play with standardized patients, direct observation, and feedback from experts. Participants completed pre- and post-intervention questionnaires with Likert-type scale and open-ended questions, which were analyzed using paired t tests and qualitative content analysis, respectively. Results: We enrolled 25 learners. The intervention was associated with an increase in knowledge ( P < .001) and self-efficacy ( P < .001). All learners reported gaining new skills, with a majority specifically identifying a framework for structuring serious illness conversations in the qualitative analysis (n = 14, 56%). Participants stated the workshops would improve their comfort in holding serious illness conversations (n = 24, 96%), and that it would be valuable to integrate the workshops into their formal curricula (n = 23, 92%). Conclusions: Training on the use of the SICG is novel for medical students and first-year residents and associated with the improvement in their knowledge of and perceived capacity to hold serious illness conversations. This study suggests that the integration of SICG training into medical curricula may have educational value.